COVID-19 Dysautonomia - Goodman, Brent P.; Khoury, Julie A.; Blair, Janis E.; Grill, Marie F. (Frontiers in Neurology, 2021)
Objective To report a case series of dysautonomia associated with COVID-19 infection. Methods This is a retrospective review of patients evaluated in the autonomic clinic at our institution with suspected signs and symptoms of dysautonomia who underwent formal evaluation, including autonomic testing. Results Six patients were identified with signs and symptoms suggestive of dysautonomia who underwent autonomic testing. All patients had symptoms typical of COVID-19 infection, though none were hospitalized for these or other symptoms. All patients reported symptoms of postural lightheadedness and near-syncope, fatigue, and activity intolerance. Five patients reported the onset of autonomic symptoms concomitant with other COVID-19 symptoms, with the other patient reporting symptom onset 6 weeks following initial COVID-19 symptoms. Autonomic testing demonstrated an excessive postural tachycardia in 4 patients, a hypertensive response with head-up tilt in 3 patients, orthostatic hypotension in 1 patient, and sudomotor impairment in 1 of the patients with excessive postural tachycardia. Conclusions We present clinical features and results of autonomic testing in 6 patients with a history COVID-19 infection. While all patients reported typical features of orthostatic intolerance, fatigue, and activity intolerance, the results of autonomic testing were heterogenous, with orthostatic hypotension in 1 patient, excessive postural tachycardia typical of postural tachycardia syndrome in 4 patients, and postural hypertension in 3 patients.